Level of job satisfaction amongst nurses in the North-West Province, South Africa: Post occupational specific dispensation - Sisinyana H. Khunou; Mashudu Davhana-Maselesele (Curationis, 2016)
Background: Job satisfaction and burnout have been recurring problems amongst nurses in the Republic of South Africa (RSA). As a result, nurses are still leaving the rural public sector in search of lucrative work at the urban and private sectors and in developed countries. Accordingly, Occupational Specific Dispensation (OSD) was introduced as a strategy to ircumvent the problem. However, since the implementation of OSD in 2007, there have been no studies conducted regarding the level of job satisfaction amongst nurses after the implementation of OSD in the North-West Province, especially because each province has its own challenges that are unique to the area.